Analisis Sistem Akuntansi Keuangan Daerah Pada Badan Pengelolaan Keuangan Dan Aset Daerah (BPKAD) Kabupaten Sarolangun - Iskandar Sam; Misni Erwati; Muhammad Febriansyah (Universitas 45 Surabaya, 2024)
This research aims to analyze the regional financial accounting system at the Sarolangun district regional financial and asset management agency office. This research lasted for 3 months. This research is qualitative research, while the data sources used in this research consist of secondary data sourced from information at the research site, scientific journals and books related to the research object and primary data obtained directly from respondents or those who are sample in this study. Data analysis in this research used the Miles & Huberman Interactive analysis technique. The results of this research show that in carrying out the main tasks and functions in the field of effective, accurate and transparent regional financial management, the Regional Financial & Asset Management Agency uses the SIMDA Finance Application and Microsoft Excel which helps manage regional government financial data. The implementation of the regional financial accounting system at BPKAD Sarolangun Regency is in accordance with Minister of Home Affairs Regulation Number 70 of 2019 concerning Regional Government Information Systems Articles 2 and 20. Preparation of BPKAD Sarolangun Regency Financial Reports consisting of: 1) Budget Realization Report, 2) Operational Report 3) Balance Sheet , 4) Equity Change Report 5) Cash Flow Report and 6) Notes to Financial Reports where the format and description of estimates have been classified in accordance with Government Regulation Number 71 of 2010 concerning Government Accounting Standards (PSAP 01) and Minister of Home Affairs Regulation Number 64 of 2013 Concerning the Implementation of Accrual-Based Government Accounting Standards in Regional Governments.